2006
DOI: 10.1080/02652030500415645
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive isotope dilution liquid chromatography/electrospray ionization tandem mass spectrometry method for the determination of acrylamide in chocolate

Abstract: Isotope dilution liquid chromatography coupled with electrospray ionization tandem mass spectrometry (LC-MS/MS) was applied to the quantification of acrylamide in chocolate matrixes (dark chocolate, milk chocolate, chocolate with nuts, chocolate with almonds, and chocolate with wheat best element). The method included defatting with petroleum ether, extracting with aqueous solution of 2 mol l À1 sodium chloride and clean-up by solid-phase (SPE) with OASIS HLB 6 cm 3 cartridges. Acrylamide was detected with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Isotope dilution has also been discussed as a means to compensate for matrix effects (14,18,19,21,23,(28)(29)(30). Although is it generally considered the most highly recommended (30) and the most versatile approach (19) for dealing with matrix effects, it has only been used in the past for the analysis of individual compounds or small groups of similar compounds and has been characterized as being costintensive and having a lack of availability (18,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotope dilution has also been discussed as a means to compensate for matrix effects (14,18,19,21,23,(28)(29)(30). Although is it generally considered the most highly recommended (30) and the most versatile approach (19) for dealing with matrix effects, it has only been used in the past for the analysis of individual compounds or small groups of similar compounds and has been characterized as being costintensive and having a lack of availability (18,24).…”
Section: Introductionmentioning
confidence: 99%
“…Still more have been developed to minimize matrix effects using different extraction, cleanup and elution techniques, including size-exclusion chromatography (18,24), solid-phase extraction (22), LC chromatographic procedures (14,22), ultra performance liquid chromatography (25), hollow fiber liquid-phase microextraction (26), flowsplitting and reduced eluent flow rates (24,27). However, most become problematic when applied to the simultaneous analysis of a broad range of compounds that encompass many different classes and structures in matrices having varying degrees of suppression and enhancement.Isotope dilution has also been discussed as a means to compensate for matrix effects (14,18,19,21,23,(28)(29)(30). Although is it generally considered the most highly recommended (30) and the most versatile approach (19) for dealing with matrix effects, it has only been used in the past for the analysis of individual compounds or small groups of similar compounds and has been characterized as being costintensive and having a lack of availability (18,24).…”
mentioning
confidence: 99%
“…In another study, the use of two-step extraction clean-up with Isolute Multimode® (non-polar C 18 and ion exchanger mixed phase) and cation-exchange cartridges was associated to significant loss of the analyte and ion suppression effect, leading to a low response of acrylamide for either coffee and cocoa powder (Delatour et al 2004). By the other hand, the use of a single-step clean-up has been successfully employed by several authors, and a variety of SPE phases have been suggested, such as Oasis® HLB (Ren et al 2006;Senyuva and Gökmen 2005), Isolute Multimode® (Granby and Fagt 2004;Delatour et al 2004), and aminopropylbonded silica (Aguas et al 2006). However, in our tests, the use of Isolute Multimode® cartridges alone did not ameliorate the MS response.…”
Section: Discussionmentioning
confidence: 97%
“…Although the methods reported in the literature for acrylamide determination in cocoa and coffee products have most commonly used water as extraction solvent (Granby and Fagt 2004;Delatour et al 2004;Aguas et al 2006;Soares et al 2006;Andrzejewski et al 2004;Ren et al 2006), the use of non-aqueous solvents was suggested based on results of the interlaboratory study conducted by BfR in 2002, which showed that the extraction of acrylamide from cocoa samples with non-aqueous polar solvents led to the assignment of almost double the amount of acrylamide compared to the extraction with water (Fauhl et al 2003). However, the results obtained in this study indicate that the use of non-aqueous solvents followed by the two SPE column clean-up steps did not improve the recovery and purification of the extract when compared to the extraction performed with water.…”
Section: Discussionmentioning
confidence: 98%
“…Over the recent years, many more papers and reviews have been published about the occurrence and analytical methods of acrylamide in heated foods (Wenzl et al 2003, Zhang et al 2005Castle and Eriksson 2005;Eberhart et al 2005;Kim et al 2007;Pittet et al 2004;Ren et al 2006). Becalski et al (2003) determined the levels and sources of acrylamide in the Canadian food supply and developed a LC-MS/MS method.…”
Section: Recent Analytical Methodsmentioning
confidence: 98%